2021
DOI: 10.3390/plants10081739
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Effects of Trichoderma Seed Inoculation on Anthracnose Disease and Seed Yield of Bean (Phaseolus vulgaris): Ambient Conditions Override Cultivar-Specific Differences

Abstract: Root colonizing Trichoderma fungi can stimulate plant immunity, but net effects are strain × cultivar-specific and changing ambient conditions further contribute to variable outcomes. Here, we used four Trichoderma spp. to inoculate seeds of four common bean (Phaseolus vulgaris) cultivars and explored in three different experimental setups the effects on fungal anthracnose after leaf inoculation with Colletotrichum lindemuthianum. Plants growing in pots with field soil under greenhouse conditions exhibited the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…The latter found that angular leaf spot resulted in yield loss ranging between 6 to 61% in unsprayed plots, while in the plots sprayed with the fungicide azoxystrobin + difenoconazole the yield loss was lower. Gutiérrez-Moreno et al [212], studied the effect of inoculating common bean seeds with four different Trichoderma strains and found that disease severity was strain-dependent. Moreover, some common bean varieties (e.g., BRS Notável) are reported to present diseases resistance (e.g., anthracnose), whilst maintaining high productivity [213].…”
Section: Disease Managementmentioning
confidence: 99%
“…The latter found that angular leaf spot resulted in yield loss ranging between 6 to 61% in unsprayed plots, while in the plots sprayed with the fungicide azoxystrobin + difenoconazole the yield loss was lower. Gutiérrez-Moreno et al [212], studied the effect of inoculating common bean seeds with four different Trichoderma strains and found that disease severity was strain-dependent. Moreover, some common bean varieties (e.g., BRS Notável) are reported to present diseases resistance (e.g., anthracnose), whilst maintaining high productivity [213].…”
Section: Disease Managementmentioning
confidence: 99%
“…Four different Trichoderma species— T. asperellum B6 [ 51 ], T. atroviride P1 [ 52 ], T. afroharzianum T22 [ 53 ] and T. longibrachiatum MK1 [ 54 ]—were analysed ( Figure 1 a). Each Trichoderma species was grown on potato dextrose agar (PDA) in 100 mm × 15 mm Petri dishes and maintained at 25 ± 1 °C in the dark with >80% humidity starting from stocks in 20% glycerol stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%